Studi Komparasi Respons Nyeri Tenggorokan Pasca Intubasi Endotracheal Tube Dan Laryngeal Mask Airway Di IBS Rumah Sakit Bhayangkara Mataram - Prayitno Prayitno; Tri Budi Santoso; Rudi Ismanto (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2020)
Background: General anesthesia is a state where loss of pain accompanied by loss of consciousness. Throat pain is an unwanted, but common, pain response due to intubation with endotracheal tube or laryngeal mask airway.Objective: To know the difference of post Intubation sore throat response condition between Endotracheal Tube and Laringeal Mask Airway Method: This research uses non experimental quantitative method with Cross Sectional design. The sampling technique used is accidental sampling. The sample in the study were 40 patients who underwent general anesthesia surgery and performed intubation with endotracheal tube or laryngeal mask airway at Rumah Sakit Bhayangkara Mataram. Data analysis is using t testResults: Each group using endotracheal tube and laryngeal mask airway were 20 respondents. The incidence of pain on endotracheal tube was 12 respondents (60%) while the laryngeal mask airway was 4 respondents (20%). t-test results obtained p value of 0.008 (p <0.05)Conclusion: There is a difference in post-extubation extro thoracic Intubation response between use of Endotracheal Tube and Laringeal Mask Airway at Rumah Sakit Bhayangkara Mataram